Enhanced emotional interference on working memory performance in adults with ADHD - Marx, Ivo; Domes, Gregor; Havenstein, Carolin; Berger, Christoph; Schulze, Lars; Herpertz, Sabine (The world journal of biological psychiatry, 2011)
Objectives. Subjects with attention-deficit/hyperactivity disorder (ADHD) suffer from both executive dysfunction and deficits in emotion regulation. However, up to now, there has been no research demonstrating a clear impact of emotional dysregulation on cognitive performance in subjects with ADHD. Methods. Male and female adults with ADHD (n=39) and gender- and IQ-matched control subjects (n=40) performed an emotional working memory task (n-back task). In the background of the task, we presented neutral and negative stimuli varied in emotional saliency (negative pictures with low saliency, negative pictures with high saliency), but subjects were instructed to ignore these pictures and to process the working memory task as quickly and as accurately as possible. Results. Compared to control subjects, ADHD patients showed both a general working memory deficit and enhanced distractability by emotionally salient stimuli in terms of lower n-back performance accuracy. In particular, while controls showed impaired WM performance when presented with highly arousing negative background pictures, a comparable decrement was observed in the ADHD group already with lowly arousing pictures. Conclusions. Our results suggest that difficulties in suppressing attention towards emotionally laden stimuli might result from deficient executive control in ADHD.
Gesehen am 11.08.2022